Perspectives towards Schoolscapes in the Deep South of Thailand: A Case Study of Two Islamic Private Schools in Yala and Pattani - Adeelah Ayae (Prince of Songkla University, 2023)
Master of Arts (Teaching English as an International Language), 2023